Steel Failure of Anchor Channels Under Fire Conditions—Proposal for a Temperature-Based Design Method - Mohamed Semlali; Omar Al-Mansouri; Christoph Mahrenholtz (Applied Mechanics, 2025)
This paper focuses on the behavior of anchor channels in the event of fire. The contribution of this project lies in the necessity coming from the market to study the fire resistance of anchor channels more thoroughly, considering the modes of failure to which they are subjected. The aim of this paper is to transform the method based on tests into a numerical method that allows calculation of the fire resistance at any time under fire conditions, for all fire scenarios (whether it is a standard fire or using performance-based design approaches). A 3D transient thermal model was developed using ANSYS 19.1 to determine the thermal distribution of anchor channels, simulated in uncracked concrete under ISO 834-1 fire conditions. Subsequently, a design model for steel-related failure modes under fire conditions was employed. The model consists of coupling the characteristic resistances of the anchor channel at ambient temperature with temperature-based reduction factors for steel-related failure modes to obtain the calculated fire resistances. The model was compared with fire test results available in the literature, and the comparison yielded satisfactory results, confirming its reliability and accuracy in capturing the relevant phenomena under fire conditions. The results of this research show that the model presents a good candidate to replace the current method of qualification of anchor channels under fire conditions.